Dampak Penggunaan QRIS Pada Pelaku UMKM di Kota Padangsidimpuan Sumatera Utara (Studi Kasus Pada Coffe Shop Kopi Koe) - Yola Afifa; M. Yarham (Niqosiya: Journal of Economics and Business Research, 2023)
All social activities, including payment systems, are experiencing very rapid changes due to digitalization and technological advances. This research is field research using qualitative methods and descriptive research type. At Koe Padangsidimpuan Café Shop, data collection methods include direct interviews with micro, small and medium business actors as well as observation and documentation techniques. Information checking strategies combine information methods, information relationships and goals. Triangulation is used during the time spent actually looking at the validity of the information. Both cafes and the general public benefit from using QRIS because it can streamline the payment system transaction process. However, the café’s income was not affected, which is a shame. Achieving the target with a small number of users shows that the impact of implementing QRIS is still below standard among millennials.